2019
DOI: 10.1111/jfpe.13022
|View full text |Cite
|
Sign up to set email alerts
|

Foam mat drying of fig fruit: Optimization of foam composition and physicochemical properties of fig powder

Abstract: In this study, we report an optimization study on fig foam composition and hot air/microwave‐assisted foam mat drying (FMD) at different conditions to produce fig powder. The effects of foam composition on foam stability and capacity were evaluated. The optimum ratio of fig, egg white, carboxymethyl cellulose, and maltodextrin was determined as 52.9, 28.9, 0.8, and 17.4% (wt/wt), respectively, targeting maximum foam capacity and minimum drainage volume, that is, maximum foam stability. The effects of drying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 44 publications
(89 reference statements)
11
44
0
2
Order By: Relevance
“…Similar results on lower drainage with higher stabilization agent concentration were reported by many previous studies. 9,17,28 Therefore, the results are consistent with the literature.…”
Section: Stabilization Of Foamssupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results on lower drainage with higher stabilization agent concentration were reported by many previous studies. 9,17,28 Therefore, the results are consistent with the literature.…”
Section: Stabilization Of Foamssupporting
confidence: 91%
“…This finding could be related to the increased viscosity of the liquid phase, which causes difficulties in trapping air in the structure. 28 Soapwort and horse chestnut extracts showed different behaviours depending on the stabilization agents. Whereas lecithin-stabilized foam prepared from soapwort had lower foam density, CMC provided a lower foam density in the foam prepared from horse chestnut extract.…”
Section: Stabilization Of Foamsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be stated that the moisture content values of the taro flours generally have an inverse proportion with the bulk density values. The bulk density values of CHAD and UP + CHAD were also in line with those obtained by Varhan et al (2019) who revealed that the bulk density values of hot air‐assisted foam mat dried fig powders changed between 0.36 and 0.50 g/cm 3 .…”
Section: Resultssupporting
confidence: 90%
“…The bulk density values of the foam mat dried taro flour ranged between 462.62 and 529.62 kg/m 3 (Table 2) which were lower than the reported values by Kaushal et al (2012) (0.689 ± 0.010 g/ml) and Njintang and Mbofung (2006) (ranged between 0.55 ± 0.01 and 0.74 ± 0.01 g/ml depending on precooking time [0–90 min] and drying temperature [50–80°C]). The highest bulk density values were observed for CHAD + MOD and UP + CHAD + MOD which are desired because of packaging and transportation costs, smaller container requirements, and the feasibility of shipping and transportation (Çalişkan Koç & Dirim, 2018; Varhan, Elmas, & Koç, 2019). Ultrasonic pretreatment (UP + CHAD and UP + CHAD + MOD) resulted in insignificant ( p > .05) lower bulk and tapped density values compared to CHAD and CHAD + MOD; however, higher bulk and tapped density values were ( p > .05) observed for UP + MOD compared to MOD.…”
Section: Resultsmentioning
confidence: 99%